Complementary and Alternative Medicine in Radiotherapy: A Comprehensive Review - Borm, Kai J.; Schiller, Kilian; Asadpour, Rebecca; Combs, Stephanie E. (Topics in Magnetic Resonance Imaging, 2020)
Complementary and alternative medicine (CAM) approaches are widely used by patients throughout a broad range of medical fields and diseases, and often self-administered by patients without the involvement of physicians or other members of the health care team. CAM use is well documented in cancer and chronic illnesses, and emerging data in radiation oncology show CAM usage of 26% to 97% in radiation therapy patients. No information is, however, available on CAM usage in radiology and in the imaging procedure fields. This article reviews the fundamental principles and the experience with the wide spectrum of CAM in radiation oncology-a field that shares many parallels with radiology, such as prevalence of imaging, procedural requirements, and cooperation demanded from patients.CAM is defined as "approaches and practices that are typically not part of conventional medical care," and includes the use of mind- and body-based practices (eg, meditation, massage, acupuncture), natural products (eg, herbs, vitamins, minerals), and other interventions. Supplements are used frequently to alleviate side effects of therapy and promote overall well-being. Specifically, the mindfulness/meditation approaches of CAM are known to reduce anxiety and enhance physical and emotional wellbeing in patients with chronic diseases, such as cancer or neurologic diseases, through physiological, psychological, and perhaps placebo mechanisms. Such patients often require repetitive and invasive imaging examinations or procedures, such as for cancer treatment, cancer surveillance/follow-up, or monitoring of chronic diseases, for example, surveillance MRI in multiple sclerosis. Such parallels suggest that the vastly understudied area of CAMs deserve further investigation in both the radiation oncology and the imaging fields. Further research on CAM is needed to develop refined recommendations and national/and international guidelines on its use.
CRIS-Team Scopus Importer:2023-03-08